Late Anisian microbe‐metazoan build‐ups in the Germanic Basin: aftermath of the Permian–Triassic crisis. (21st July 2021) - Pei, Yu; Duda, Jan‐Peter; Schönig, Jan; Luo, Cui; Reitner, Joachim
Abstract : The so‐called Permian–Triassic mass extinction was followed by a prolonged period of ecological recovery that lasted until the Middle Triassic. Triassic stromatolites from the Germanic Basin seem to be an important part of the puzzle but have barely been investigated so far. Here, we analysed late Anisian (upper Middle Muschelkalk) stromatolites from across the Germanic Basin by combining petrographic approaches (optical microscopy, micro X‐ray fluorescence, Raman imaging) and geochemical analyses (sedimentary hydrocarbons, stable carbon and oxygen isotopes). Palaeontological and sedimentological evidence, such as Placunopsis bivalves, intraclasts and disrupted laminated fabrics, indicate that the stromatolites formed in subtidal, shallow marine settings. This interpretation is consistent with δ 13 Ccarb of about −2.1‰ to −0.4‰. Occurrences of calcite pseudomorphs after gypsum possibly suggest occasionally elevated salinities, which is well in line with the relative rarity of fossils in the host strata. Remarkably, the stromatolites are composed of microbes (perhaps cyanobacteria and sulphate‐reducing bacteria) and metazoans such as non‐spicular demosponges, Placunopsis bivalves and/or microconchids. Therefore, these 'stromatolites' should more correctly be referred to as microbe‐metazoan build‐ups. They are characterized by diverse lamination types, including planar, wavy, domal and conical ones. Microbial mats likely played an important role in forming the planar and wavy laminations. Domal and conical laminations commonly show clotted to peloidal features and mesh‐like fabrics, attributed to fossilized non‐spicular demosponges. Our observations not only point up that non‐spicular demosponges are easily overlooked and might be mistakenly interpreted as stromatolites, but also demonstrate that microbe‐metazoan build‐ups were widespread in the Germanic Basin during Early to Middle Triassic times. In the light of our findings, it appears plausible that the involved organisms benefited from elevated salinities. Another (not necessarily contradictory) possibility is that the mutualistic relationship between microbes and non‐spicular demosponges enabled these organisms to fill ecological niches cleared by the Permian–Triassic crisis. If that is to be the case, it means that such microbe‐metazoan associations maintained their advantage until the Middle Triassic.